Study on the Artistic Characteristics and Inheritance Paths of Jiaozuo Huai Bangzi Opera (Journal of Global Arts Studies, 2025)
Background： Jiaozuo Huai Bangzi Opera originated in Huaiqing Prefecture during the Yongle period of the Ming Dynasty, with its predecessor being Haishen Opera. It integrates Shanxi opera elements and local culture, and is divided into East Road and West Road schools. As a national intangible cultural heritage, it is now only performed in rural areas during festivals, and current academic research on the detailed analysis of its artistic characteristics and systematic inheritance remains insufficient. Objective： To systematically expound the artistic characteristics and multiple values of Jiaozuo Huai Bangzi Opera, sort out its development dilemmas, and propose targeted protection and inheritance strategies. Methods： The literature research method was adopted, including online database retrieval and offline historical data collection, combined with the collation and analysis of existing research results. Results: The core characteristics of its role singing, accompanying instruments (such as Daxian, Yueqin) and banzhi tunes were clarified; three types of values (cultural, aesthetic, folk) were summarized; and dilemmas such as talent shortage, government support measures and diversified inheritance plans were sorted out. Conclusion: Jiaozuo Huai Bangzi Opera needs improvement to adapt to the times. Its inheritance has both opportunities and challenges, and continuous exploration is required to enhance public awareness and promote the living protection of this intangible cultural heritage project.
Keywords: Huai Bangzi Opera; Artistic Characteristics; Banzhi tunes; Inheritance